Edukasi Penanganan Sumbatan Jalan Napas Oleh Benda Asing pada Anak Usia 2-5 Tahun Menggunakan Teknik Heimlich Maneuver - Maitsa, Hilvi; Yudono, Danang Tri; Yudha, Magenda Bisma (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Choking in young children occurs when a foreign object enters the airway and blocks the flow of oxygen. This condition is dangerous because it can cause hypoxia and even death. One effective treatment is first aid using the Heimlich maneuver technique. Objective: This community service program aims to determine the level of knowledge and skills of mothers in managing airway obstruction caused by foreign objects in children aged 2–5 years using the Heimlich maneuver in Randegan Village, Wangon District. Method: This community service program was conducted through education using audiovisual media, distribution of leaflets, and pre-tests and post-tests to measure the participants' level of knowledge. The activity was attended by 30 mothers who had children aged 2–5 years in Randegan Village, Wangon District. Result: The results showed that before the education, the majority of participants had insufficient knowledge (14 participants or 46.7%) and unskilled skills (20 participants or 66.7%). After the education, good knowledge increased to 23 participants (76.7%) and skilled skills to 25 participants (83.3%). Statistical analysis showed that the increase in knowledge and skills was significant (p < 0.05). Conclusion: Education has been proven to improve mothers' knowledge and skills in handling airway obstruction in toddlers using the Heimlich maneuver technique.